Perbaikan Min-Max Distribusi Dengan Multiple Criteria ABC Analysis NG-Model Untuk Pengoptimalan List Part Number - Hanif, Zulhendra; Hisjam, Muhammad; Jauhari, Wakhid Ahmad (Jurnal Ilmiah Teknik Industri, 2019)
PT GMF Aeroasia Tbk. is the largest MRO company in Indonesia. This company has 67 plants worldwide. With the many plants that must be serviced, the complex process of repairing aircraft with spare parts that exceeds 15,000 types. Part distribution is a very big challenge and must be faced by companies where part distribution is done with multi-stage warehouses. At present the main warehouse has problems with the inefficiency of the min-max distribution system at each plant where the system aims to bond the parts that have the greatest frequency of demand to the sub-warehouse at the plant. This study discusses the improvement of Min-Max distribution with ABC Analysis NG-Model Multiple Criteria which aims to improve the efficiency of the list part number with the frequency of order transfer requests and the most optimal performance at 9 internal plants with the largest part demand activity. The proposed method is known to be able to increase min-max accommodation including, Transfer Order frequency from 23% to 40.80% and weekly delivery performance from 22% to 62.69%. In addition, this method can also reduce the amount of part number on Min-max with the results of Transfer Order accommodation and increased performance from the methods currently used.